Experimental Demonstration of Fine-Grained Steering Inequality of Two-Qubit Mixed States - Zhi-Hao Bian; Cong-Yue Yin (Photonics, 2021)
Quantum steering, as a cornerstone of quantum information, is usually used to witness the quantum correlation of bipartite and multi-partite states. Here, we experimentally demonstrate the quantum steering inequality of two-qubit mixed states based on the fine-grained uncertainty relation. Our experimental results show that the steering inequality has potent sensitivity to Werner states and Bell diagonal states. The steering strategy exhibits a strong ability to identify that Werner states are steerable when the decoherence coefficient <semantics>a>12</semantics>. Compared to the steering inequality obtained by another stratagem, the steering witness criteria of mixed states based on the fine-grained uncertainty relation demonstrated in our experiment has better precision and accuracy. Moreover, the detection efficiency in our measurement setup is only required to be <semantics>50%</semantics> to close the detection loophole, which means our approach needs less detector efficiency to certificate the steerability of mixed states.